Business Models for Technology-Intensive Supply Chains - Lee, Junghee; Krishnan, Vish; Shin, Hyoduk (Management Science, 2020)
Technology and intellectual property play increasingly critical roles in emerging supply chains by endowing products with sought-after capabilities. In such technology-intensive supply chains, the technology invented by an upstream firm must be embedded in a subsystem that is then integrated into a full system. The technology providers’ prevalent royalty-driven business model has gotten complicated in this multilateral supply chain, prompting formal research attention. Moreover, providers also consider forward integration into manufacturing to monetize their intellectual property. We characterize the appropriateness of different business model decisions for markets, which may have varying levels of consumer diversity and competitive intensity at intermediate layers. For the technology provider, our key results show that a subsystem base royalty approach is the optimal business model when dealing with monopolistic intermediaries or having a low degree of consumer diversity. However, a full-system base royalty business model becomes increasingly optimal when the intermediate supply chains face competition and consumer diversity increases. We present conditions under which the technology provider may want to forward integrate. Our formulation and results are relevant to technology providers, policy makers, and industry groups engaged in the prevailing heated global discussion on royalty base. This paper was accepted by Serguei Netessine, operations management.